2016
DOI: 10.1093/brain/aww056
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ganglioside antibodies are removed from circulation in mice by neuronal endocytosis

Abstract: See van Doorn and Jacobs (doi:) for a scientific commentary on this article.   How does anti-ganglioside autoantibody clearance from the circulation affect their detection and neurotoxicity? Cunningham et al. describe an uptake pathway for these autoantibodies at motor nerve terminals and their delivery into the brain parenchyma. This highlights the limitations of serum antibody measurements and suggests a possible entry mechanism for their central effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
1
16
1
Order By: Relevance
“…Due to the discrepancies in antibody presence between results from serology and high-throughput screening of hybridoma supernatant, we also investigated whether anti-sulfatide antibodies were removed from the circulation via endocytic uptake, using GAME-G3 as a representative antibody. In contrast to a previous study using anti-ganglioside antibodies ( Cunningham et al, 2016 ), comparisons of CST −/− and CST +/+ indicated that the antibodies were not removed from the circulation by sulfatide-mediated endocytosis. Despite the mechanism of antibody clearance remaining unknown, the discrepancy between detectable levels of IgG in the serum and in hybridoma supernatant highlights the importance that serum levels of antibody do not represent the repertoire of antibodies being produced ( Cunningham et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Due to the discrepancies in antibody presence between results from serology and high-throughput screening of hybridoma supernatant, we also investigated whether anti-sulfatide antibodies were removed from the circulation via endocytic uptake, using GAME-G3 as a representative antibody. In contrast to a previous study using anti-ganglioside antibodies ( Cunningham et al, 2016 ), comparisons of CST −/− and CST +/+ indicated that the antibodies were not removed from the circulation by sulfatide-mediated endocytosis. Despite the mechanism of antibody clearance remaining unknown, the discrepancy between detectable levels of IgG in the serum and in hybridoma supernatant highlights the importance that serum levels of antibody do not represent the repertoire of antibodies being produced ( Cunningham et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 98%
“…Interestingly, hybridoma screening revealed the presence of IgG antibodies, which were not detected in mouse serum. We therefore considered that any circulating anti-sulfatide antibodies might be actively depleted from the circulation through a receptor-dependent endocytosis clearance mechanism, as previously observed for anti-ganglioside antibodies ( Cunningham et al, 2016 ). To investigate this, CST +/+ and CST −/− mice were passively immunised with 250 μg/ml of GAME-G3 and bled at days 1, 3, 6 and 7 to monitor serum levels of anti-sulfatide antibodies ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from affinity, the level of anti-GalC IgG may be critical for the initiation of M. pneumoniae-associated neurological disease. It is possible that low levels of GalC IgG are removed from the circulation by targetmediated clearance (57). Interestingly, B-1a cells triggered by glycolipid antigens can also undergo activation-induced deaminase-dependent class switching (43).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report of ganglioside-antibody removal by neuronal endocytosis as shown in a mouse model is an interesting observation and further strengthens the notion that antibodies may gain access to intracellular synaptic proteins. (16) GAD-antibodies GAD-antibodies, the most frequent in SPSD, also target an intracellular, synaptic antigen. GAD is the rate limiting enzyme in the synthesis of gamma-aminobutyric acid (GABA), a major inhibitory neurotransmitter (Fig.1).…”
Section: Amphiphysin-antibodiesmentioning
confidence: 99%